The Effect of Gatot (Fermented Dried Cassava) and Red Bean Ratio on Water Content and Organoleptic Characteristics of The "Gatotkaca" Analog Rice - Eries Kusmiandany; Yoga Pratama; Yoyok Budi Pramono (Journal of Applied Food Technology, 2019)
This study aimed to evaluate the effect of the ratio of gatot and red beans usage on water content and organoleptic characteristics from "Gatotkaca" analog rice. The material in this study was gatot (fermented cassava) and red beans. The experimental design used was a completely randomized design (CRD) with 4 treatments and 5 replications. This study consisted of 4 different analog rice formulations, namely T1 (90% gatot: 10% red beans); T2 (85% gatot: 15% red beans); T3 (80% gatot: 20% red beans); T4 (75% gatot: 25% red beans). Data were analysed using Analysis of Variance (ANOVA) with the significance level 5%. The results showed that the difference in the ratio of the usage of gatot but red beans didn’t have a significant effect (p>0.05) on the water content and organoleptic characteristics. Treatment with a ratio of gatot and 85% red beans  15% gatot was the best treatment.